Effect of Work Culture and Leadership on Trust in PT. Astra Agro Lestari Tbk. - Pandapotan Sitompul; Suparno Eko Widodo; R. Madhakomala (Program Studi S3 Ilmu Manajemen, 2018)
The purpose of this study was to study the effect of work culture, leadership on trust. The research process was carried out at PT. Astra Agro Lestari Tbk. uses a case study method. The study sample was 105 employees of PT. Astra Agro Lestari Tbk. selected in simple random sampling. The findings are: (1) there is a positive direct influence of work culture on trust, (2) there is a positive direct influence of leadership on trust, (3) there is a positive direct influence of work culture and leadership together on trust. Referring to these findings, researchers can conclude that trust is positively influenced by work culture and leadership. Therefore, to maintain trust, organizations must implement a work culture and leadership. Finally, it was concluded that work culture and leadership must be considered in generating better trust.